A Historiographical Survey of ”Ius Valachicum” among Romanians and Vlachs - Cosma, Ela (Balcanica Posnaniensia. Acta et studia, 2023)
The purpose of our study is to investigate the current state of research regarding Ius Valachicum in Romanian and foreign historiography. After presenting Romanian history, palaeography and the legal history of the Carpatho-Danubian space, we turn to the Polish historiography of the North Vlachs, with respect to the Serbo-Croatian historiography of the South Vlachs. Finally, we use case studies to illustrate two enacted customary laws of the Vlachs from Croatia. The methods used in this paper include description, analysis, and comparison, as well as exploratory and applied research. The article is a historiographical survey of Ius Valachicum among the Romanians and Vlachs. The medieval and premodern consuetudinary laws of the Romanians and Vlachs are reflected both in primary and secondary sources, from 14thcentury historical documents to historiographical preoccupations dedicated to Ius Vlachicum from the 18thand 19th centuries. First, we refer to the special literature explaining both ethnonyms and the historical-geographical spread of the Romanians and Vlachs. Then we present the Romanian historiography investigating the manifestations and features of Ius Valachicum in the geographical area belonging to the present-day Romanian state. Turning to the Czech and Polish historiography, the occurrence of Ius Valachicum is revealed among the North Vlachs from medieval and premodern Poland, Ruthenia, and Hungary. We also review the Serbo-Croatian historiography of the Ius Valachicum specific to the South Vlachs from Croatia and Serbia. Finally, two enacted customary laws of the Vlachs from Croatia (1436, 1630) are analysed from the point of view of legal history. These codifications of Ius Valachicum prove the juridical power and importance acquired by the Croatian Vlachs during the Middle Ages. The historiographical pros and cons, as well as the critical remarks presented at the end of this study, at the same time, offer a few methodological solutions for future investigations of Romanian and Vlach Ius Valachicum.